Polyvinylidene fluoride-based dual-layer hollow fibre nanocomposite membranes for membrane distillation - Ravi, Jeganes (2021)
Membrane distillation (MD) is a technology that makes use of the temperature difference created across the membrane. One of the main challenges in MD research is to fabricate membranes with high wetting resistance and high permeate flux. To date, very limited work has reported on the use of both hydrophobised carbon-based nanoparticles and hydrophobicity gradient in achieving those qualities. Thus, this work was focused on the fabrication of dual-layer hollow fibre polyvinylidene fluoridebased nanaocomposite membranes with hydrophobic gradient. The nanocomposite membranes were incorporated with hydrophobised nanoparticles, i.e. multi-walled carbon nanotube (MWCNT) and graphene nanoplatelet (GNP). The effect of different concentrations of nanoparticles (1 and 2 wt%) on the performance of the membranes was investigated as well. The nanoparticles were oxidised with concentrated nitric acid and sulphuric acid, hydrophobised with 1H,1H,2H,2H-perfluorodecyltriethoxysilane and characterised to confirm the hydrophobisation and determine their specific surface area. The hydrophobicity gradient was created by introducing the hydrophobised nanoparticles in the outer layer dope solution and hydrophilic polyethylene glycol in the inner layer dope solution. The dual-layer membranes were then fabricated and characterised to determine their wetting resistance, chemical composition, surface and cross-sectional morphology, pore size, porosity and contact angle before their performances were tested in a direct contact membrane distillation (DCMD) set-up. MWCNT and GNP were successfully oxidised and hydrophobised as confirmed by energy-dispersive X-ray spectroscopy (EDX) and Fourier transform infrared spectroscopy (FTIR) results. Both the hydrophobised nanoparticles had smaller Brunauer-Emmett-Teller (BET) specific surface area as compared to the pristine nanoparticles. All the fabricated membranes had an asymmetrical structure with finger-like and sponge-like pores in the inner and outer layers respectively. The outer layers of the nanocomposites membranes were hydrophobic and the membrane with 2 wt% of hydrophobised GNP had the highest contact angle of 111.1°. All the inner layers of the membranes were found to be hydrophilic, thus proving that hydrophobicity gradients were achieved in the membranes. The surface roughness, contact angle and wetting resistance of all the nanocomposite membranes were higher than the neat membrane and the values increased with increasing concentration of nanoparticles. Membranes incorporated with GNP showed better performance in terms of contact angle and wetting resistance. All the nanocomposite membranes showed better DCMD performance than the neat membrane. The membrane incorporated with 2 wt% of hyrophobised GNP achieved the highest flux of 8.27 kg/(m2h) at feed temperature of 80?. All the membranes achieved a salt rejection of more than 99%. Nonetheless, the flux of the membranes were quite low compared to the flux of membranes reported in the literature, likely due to small pore sizes and dense interfaces.